Potensi Strategi Problem-based Learning (PBL) Terintegrasi Reading Questioning And Answering (RQA) Untuk Meningkatkan Hasil Belajar Kognitif Mahasiswa Berkemampuan Akademik Berbeda - Arsad Bahri; Aloysius Duran Corebima; Mohamad Amin; Siti Zubaidah (Universitas Negeri Malang, 2017)
Abstract: The aim of this research was to determine the effect of PBL, RQA, PBLRQA, and conventional learning on cognitive learning outcome of students with different academic level in Basic Biology classroom. This research was a quasy experiment with pretest-posttest control group design. Cognitive learning outcome was measured by essay test. Data were analysed with descriptive and inferential statistics with ANCOVA. The result of research showed that: 1) learning strategy and academic level effected on cognitive learning outcome. PBLRQA had the potency to improve cognitive learning outcome greater than others strategy, 2) cognitive learning outcome of students with higher academic level was higher than lower academic level, 3) interaction between learning strategy and academic level did not effect on cognitive learning outcome. PBLRQA could use as basic of development of Biology learning strategy and others subject. Key Words: Problem-based learning, reading questioning answering, cognitive learning outcome, academic level, basic biology Abstrak: Penelitian ini bertujuan untuk menjelaskan pengaruh PBL, RQA, PBLRQA, dan pembelajaran konvensional terhadap hasil belajar kognitif mahasiswa berkemampuan akademik berbeda pada perkuliahan Biologi Dasar. Penelitian ini merupakan penelitian eksperimen semu dengan desain pretest-posttest control group design. Hasil belajar kognitif diukur menggunakan tes essay. Data dianalisis secara deskriptif dan inferensial dengan anakova. Hasil penelitian menunjukkan bahwa: 1) strategi pembelajaran dan kemampuan akademik berpengaruh terhadap hasil belajar kognitif. PBLRQA berpotensi meningkatkan hasil belajar kognitif dibandingkan strategi lainnya, 2) hasil belajar kognitif mahasiswa berkemampuan akademik atas lebih tinggi daripada kemampuan akademik bawah, 3) interaksi antara strategi dengan kemampuan akademik tidak berpengaruh terhadap hasil belajar kognitif. PBLRQA dapat digunakan sebagai dasar pengembangan strategi pembelajaran Biologi dan pembelajaran lainnya. Kata kunci: Problem-based learning, reading questioning answering, hasil belajar kognitif, kemampuan akademik, biologi dasar